2013
DOI: 10.1097/bpo.0b013e318287f728
|View full text |Cite
|
Sign up to set email alerts
|

Serial Ultrasound Evaluation of Pediatric Trigger Thumb

Abstract: Level 2 diagnostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 21 publications
0
18
0
3
Order By: Relevance
“…Interestingly, the authors noted that 2 patients with unilateral triggering had an enlarged FPL tendon on the initially unaffected side later began triggering, which suggested that ultrasound was a potential early diagnostic tool. 13 Plain radiographs are generally not indicated when the history and clinical examination are consistent with a trigger thumb.…”
Section: Clinical Picture Trigger Thumbmentioning
confidence: 99%
“…Interestingly, the authors noted that 2 patients with unilateral triggering had an enlarged FPL tendon on the initially unaffected side later began triggering, which suggested that ultrasound was a potential early diagnostic tool. 13 Plain radiographs are generally not indicated when the history and clinical examination are consistent with a trigger thumb.…”
Section: Clinical Picture Trigger Thumbmentioning
confidence: 99%
“…Se ha demostrado que es una alteración del desarrollo, 9,2,1 porque al nacimiento el tendón es de tamaño normal, pero en los primeros 3 años de vida se va engrosando. 10,11,9 En 25 a 30% de los casos ocurre afectación bilateral, 2 aunque no suele manifestarse al mismo tiempo. 5 Existen reportes de familias que muestran un patrón de herencia dominante con penetrancia variable, 7 pero no existe predisposición por género; a diferencia del resto de los dedos, el pulgar en gatillo no se relaciona con alteraciones sistémicas.…”
Section: Figuraunclassified
“…pokazuju da škljocavi palac nastaje kada poprečni presjek tetive fleksora nadmaši mogućnost prilagodbe poprečnog presjeka ovojnice na razini A1 pulleya. 17 Kim i sur. s pomoću najnovijeg ultrazvučnog mjerenja poprečnog presjeka tetive nalaze prosječno 77% veću površinu poprečnog presjeka tetive proksimalno od A1 pulleya u odnosu prema površini ispod njega.…”
Section: Etiologija I Patofiziologijaunclassified
“…Nalaz zadebljale, potpuno homogene vlaknaste tetive postavlja dijagnozu škljocavog palca. 17 Prema Hülsemannu i sur., četiri su bitna klinička entiteta slična škljocavom palcu. 31…”
Section: Diferencijalna Dijagnozaunclassified